ASSESSMENT OF PHARMACIST MEDIATED EDUCATION ON MEDICATION ADHERENCE BEHAVIOR IN TYPE 2 DIABETES MELLITUS PATIENTS IN SOUTH INDIAN RURAL POPULATION - Adepu, Sai Pawan Ramesh; Sam, Steny; Omanakuttan, Cuckoo; K V, Ramanatha; Yashaswini, Yegurla (International Journal of Pharmacy and Pharmaceutical Sciences, 2018)
Objective: To assess the influence of pharmacist mediated education on medication adherence behavior (MMAS-8) in rural patients with type 2 diabetes mellitus. Methods: This is a prospective, randomized interventional study approved by the institutional ethics committee. Eligible type 2 diabetic patients with written informed consent were enrolled and randomized into control and test group. The MMAS-8 questionnaire was administered to all patients at baseline and three subsequent follow-ups. Patients in the test group received structured education at every follow-up, whereas the control group patients received education only at the final follow up. SPSS software was used to evaluate the data. Results: Among the 72 patients enrolled, 35 were randomized into a control group and 37 into the test group. Majority of the study patients (65.2%) were males with an age range of 30 to 72 y and were from agriculture profession (34.72%) with school education (59.7%). The mean body mass index (BMI) of the study patients was 25.01. At baseline, the mean glycosylated hemoglobin (HbA1c) value of patients was 6.48Â±1.39% in the control group and 6.23Â±1.16% in the test group. During the last follow-up, a significant (p<0.05) improvement was observed in MMAS-8 scores in test group patients compared to control group patients which were supported by statistically significant (p<0.05) improvement in capillary blood glucose (CBG) values. Conclusion: Pharmacist mediated structured education has shown a positive impact on medication adherence behavior of test group patients towards their disease management.